Acid-stable capsid structure of Helicobacter pylori bacteriophage KHP30 by single-particle cryoelectron microscopy - Kamiya, Ryosuke; Uchiyama, Jumpei; Matsuzaki, Shigenobu; Murata, Kazuyoshi; Iwasaki, Kenji; Miyazaki, Naoyuki (Structure (London), 2022)
The acid-stable capsid structures of Helicobacter pylori phages KHP30 and KHP40 are solved at 2.7 and 3.0 Å resolutions by cryoelectron microscopy, respectively. The capsids have icosahedral T = 9 symmetry and consist of each 540 copies of 2 structural proteins, a major capsid protein, and a cement protein. The major capsid proteins form 12 pentagonal capsomeres occupying icosahedral vertexes and 80 hexagonal capsomeres located at icosahedral faces and edges. The major capsid protein has a unique protruding loop extending to the neighboring subunit that stabilizes hexagonal capsomeres. Furthermore, the capsid is decorated with trimeric cement proteins with a jelly roll motif. The cement protein trimer sits on the quasi-three-fold axis formed by three major capsid protein capsomeres, thereby enhancing the particle stability by connecting these capsomeres. Sequence and structure comparisons between the related Helicobacter pylori phages suggest a possible mechanism of phage adaptation to the human gastric environment. [Display omitted] •Cryo-EM capsid structures of Helicobacter pylori phages KHP30 and KHP40•Phage capsid structures in T = 9 icosahedral symmetry•Structural insights into particle stability in acid conditions•Possible mechanism of phage adaptation to the human gastric environment Kamiya et al. solve the capsid structures of Helicobacter pylori phages KHP30 and KHP40 in atomic detail. The structures reveal the capsid stability mechanism in highly acidic conditions. Sequence and structure comparisons between the related phages suggest a possible mechanism of phage adaptation to the human gastric environment.